Vólvulo da vesícula biliar tratado por colecistectomia laparoscópica - Coelho,Júlio Cezar Uili (2001)
Our objective is to report a case of gallbladder torsion treated by laparoscopic cholecystectomy. A 87 year old patient presented with intense right upper quadrant pain, anorexia, nausea and vomiting. Murphy's sign was present at physical examination. Hemogram showed 9.200 leukocytes/mm³, with six bands. Ultrassonography showed a distended gallbladder, perivesicular fluid collection, wall edema, and sludge with stones inside. At laparoscopic cholecystectomy, there was a complete gallbladder torsion with areas of necrosis. There was no postoperative complication. Pathologic examination confirmed the diagnosis of acute calculous cholecystitis with areas of necrosis.